Effectiveness Of Breastfeeding Educatiuon Class (TO) On Improving Maternal Self-Efficacy Post Partum At Sangurara Health Center Year 2023 - Nurhaeda Nurhaeda; Farida Farida (The International Science of Health Journal, 2023)
Self-efficacy is a person’s belief about his or her ability to produce a planned level of performance in carrying out a series of actions that are consideret nnecessary to achieve the desired results. Providing Educational Classes (KE) to post partum mothers using modules on the importance of breast milk for babies so that this can increase the efficacy of mothers in breastfeeding their babies at the beginning og the postpartum priode 0-7 days. This study aims to determine the effectivebess of brestfeeding education classes on increasing the self-efficacy of postpartum mothers at UPT Puskesmas Sangurara in 2023. This type of research is a quast experiment with a two group pretest-posttest design. the number of sampel was 30 respondents (15 control group respondents who received questionnaires withhout educational classes and 15 intervention group respondents who received educational classes and questionnaires). Sampel were obtained using purposive sampling technique. Evaluastion of maternal efficacy was carried out on day 7 post partum both control and intervention groups. The results of this study indicate the of an increase in efficacy in the control group and the intervention group. Where in the control group there is a difference of 1.48 before and after being give educational classes and the interventional group there is a difference of 2.94 before and after being given educational classes. Based on the results of the paired T test, the value of ?= 0.00< ?=0.05 shows that there is on difference in the average before and after being given educational classes but there is a difference between the control group and the intervetion group so it can be concluded that educational classes are effective in increasing the efficacy of partum mothers.